2021
DOI: 10.1097/mao.0000000000003258
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Cochlear Implantation After Translabyrinthine Vestibular Schwannoma Resection: A Report of 41 Cases

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 47 publications
0
30
1
Order By: Relevance
“…At 1-year follow-up, 48.8% of patients were CI users compared with 51.2% nonusers. In the user group, the sentence recognition score was 31% at activation and 61% at 12-month follow-up, in contrast to nonusers who demonstrated sentence recognition scores of 2.9 and 15.3%, respectively (1). Furthermore, a recent systematic review looking at the outcomes of concurrent CI and translabyrinthine removal of VS found that 85% of patients achieved audibility through the CI.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…At 1-year follow-up, 48.8% of patients were CI users compared with 51.2% nonusers. In the user group, the sentence recognition score was 31% at activation and 61% at 12-month follow-up, in contrast to nonusers who demonstrated sentence recognition scores of 2.9 and 15.3%, respectively (1). Furthermore, a recent systematic review looking at the outcomes of concurrent CI and translabyrinthine removal of VS found that 85% of patients achieved audibility through the CI.…”
Section: Discussionmentioning
confidence: 95%
“…Recent successes with simultaneous cochlear implantation and resection of vestibular schwannoma (VS) and evolving indications for cochlear implant (CI) use in single-sided deafness have expanded the available management options for patients with VS and nonserviceable hearing. (1,2). If simultaneous or subsequent CI is being considered for patients managed with microsurgical resection, intraoperative anatomic and functional preservation of the cochlear nerve is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data, both from the adult single-sided deafness literature and within the VS population, indicate that cochlear implantation may ameliorate many of these deficits by reinstating binaural cues. 6,7,9,10 As a requisite for cochlear implantation in the VS population, the cochlear nerve must be anatomically intact and sufficiently healthy to transmit an electrical signal, and the cochlea must be largely patent for electrode placement. Implantation in this population is particularly appealing for patients with neurofibromatosis type 2 or contralateral hearing loss from unrelated factors.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study including 41 patients undergoing simultaneous TL VS resection and cochlear implantation reported that 81% of patients achieved sound perception and 49% remained long-term device users. 9 If cochlear implantation is being considered within the context of TL surgery, concomitant device placement (or at a minimum a cochlear spacer) is advisable given the high prevalence of early cochlear obliteration with this approach compared to others. 34 While the cochlear nerve can be anatomically preserved in both a TL and RS approach, the cochlea is less likely to develop early prohibitive ossification following the RS approach, effectively offering two opportunities to preserve or restore ipsilateral hearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation